Community Building by Connecting Local Skills and Knowledge - Biradar, B. S.; Butdisuwan, Sujjin (Journal of Information and Knowledge, 2010)
In this emerging knowledge society libraries should extend their services and outreach programs to the rural dwellers in real sense. For the same, department of Public libraries need to plan about capturing of local skill and knowledge for extensive utilization by rural dwellers. Therefore this paper concentrates mainly on community building What? Why? and How. Much emphasis is given on role of community information centres in community building.